2020
DOI: 10.18632/aging.103467
|View full text |Cite
|
Sign up to set email alerts
|

Pan-metastatic cancer analysis of prognostic factors and a prognosis-based metastatic cancer classification system

Abstract: We aimed to perform a pan-metastatic cancer analysis on survival and prognostic factors and to create a prognosis-based classification system. We selected distant metastasis patients from the Surveillance, Epidemiology, and End Results (SEER) database. The associations between the characteristics of the patients at admission and overall survival were determined. A prognosis-based metastatic cancer classification was established based on the identified prognostic factors. The differences in prognosis among thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…They suggested the surgery was negatively associated with all causes of death risk for metastatic rectal cancers after adjusting for age, sex, and other clinical characteristics. 22 Consistent with these studies, our study also confirmed negative associations between surgery on the primary site and all causes of mortality, even in patients with distant metastasis and patients with advanced age (>80 years). We also suggest the surgery could not prolong the survival in patients with four organ metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…They suggested the surgery was negatively associated with all causes of death risk for metastatic rectal cancers after adjusting for age, sex, and other clinical characteristics. 22 Consistent with these studies, our study also confirmed negative associations between surgery on the primary site and all causes of mortality, even in patients with distant metastasis and patients with advanced age (>80 years). We also suggest the surgery could not prolong the survival in patients with four organ metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Zhang and colleagues conducted a pan-cancer analysis of the prognostic factors for metastatic cancer. They suggested the surgery was negatively associated with all causes of death risk for metastatic rectal cancers after adjusting for age, sex, and other clinical characteristics [20]. Consistent with these studies, our study also con rmed negative associations between surgery on the primary site and all causes of mortality, even in patients with distant metastasis and patients with advanced age (> 80 years).…”
Section: Discussionsupporting
confidence: 91%
“…In the current literature, hierarchical clustering has been also used to classify various patients with pan-metastatic cancers. Zhang and his teammates [ 29 ] used hierarchical clustering analysis to construct a classification system based on survival and prognostic factors, thus dividing stage IV metastatic patients into three categories. This approach helps provide a novel strategy for guiding the prediction of survival and personalized treatment for stage IV metastatic patients.…”
Section: Discussionmentioning
confidence: 99%